PENGELOLAAN WILAYAH PESISIR DENGAN PROGRAM PUMP-P2HP BIDANG PENGOLAH DAN PEMASAR HASIL PERIKANAN UNTUK PEMBERDAYAAN MASYARATAKAT PESISIR PANTAI KOTA PADANG - YOVY IRFANOLLA; Widya Prarikeslan (JURNAL BUANA, 2020)
Study of Coastal Area Management With the PUMP-P2HP Program in the Processing and Marketers of Fisheries Products for Empowering Coastal Communities in Padang City, this study aims to find out 1). The shape of the pattern of distribution of processors and marketers of fishery products and why this pattern can occur in the Coastal Areas of Kota Padang 2). Quantity of revenue and production results in the field of processed fishery recipients of the program before and after the implementation of PUMP in the P2HP field in Padang City. This type of research is a descriptive study with survey methods and quantitative analysis. The population of this research is 54 groups (Polakhsar) in 6 Districts of Padang's coastal area. The sampling technique in this study is total sampling. Based on the results of the study found 1.) The distribution pattern of the Polakhsar fishing group with cluster pattern with an index value of T 0.043743 and influenced by geographic spatial interactions of complementary interactions and transferability. 2). The income of the Polakhsar group in the processed fish sector prior to the PUMP-P2HP program and after the PUMP-P2HP program was that the total production of Polakhsar fishery products from 2014-2018 increased by 23% and the income of the Polakhsar group increased by 31% in the coastal area Padang city.